A Platform-Based Methodology for System-Level Mixed-Signal Design. (22nd March 2010) - Nuzzo Nuzzo, Pierluigi Pierluigi; Sun Sun, Xuening Xuening; Wu Wu, Chang-Ching Chang-Ching; De Bernardinis De Bernardinis, Fernando Fernando; Sangiovanni-Vincentelli Sangiovanni-Vincentelli, Alberto Alberto
Abstract : The complexity of today's embedded electronic systems as well as their demanding performance and reliability requirements are such that their design can no longer be tackled with ad hoc techniques while still meeting tight time to-market constraints. In this paper, we present a system level design approach for electronic circuits, utilizing the platform-based design (PBD) paradigm as the natural framework for mixed-domain design formalization. In PBD, a meet-in-the-middle approach allows systematic exploration of the design space through a series of top-down mapping of system constraints onto component feasibility models in a platform library, which is based on bottom-up characterizations. In this framework, new designs can be assembled from the precharacterized library components, giving the highest priority to design reuse, correct assembly, and efficient design flow from specifications to implementation. We apply concepts from design centering to enforce robustness to modeling errors as well as process, voltage, and temperature variations, which are currently plaguing embedded system design in deep-submicron technologies. The effectiveness of our methodology is finally shown on the design of a pipeline A/D converter and two receiver front-ends for UMTS and UWB communications.